2016
DOI: 10.22581/muet1982.1604.06
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Touch Collaborative Gesture Recognition Based User Interfaces as Behavioral Interventions for Children with Autistic Spectrum Disorder: A Review

Abstract: This paper addresses UI (User Interface) designing based on multi-touch collaborative gesture recognition meant for ASD (Autism Spectrum Disorder)-affected children. The present user interfaces (in the context of behavioral interventions for Autism Spectrum disorder) are investigated in detail. Thorough comparison has been made among various groups of these UIs. Advantages and limitations of these interfaces are discussed and future directions for the design of such interfaces are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…To ensure the naturalness of a VE, the interface of a VR application should be consistent and coordinated [6]. Interactions by the traditional interactive tools like keyboard and mouse are insufficient and lag behind to completely involve the users [7][8] in interactive 3D VE. As hand gestures are adaptable and flexible, hence suitable for interactions in a VE [2,9].…”
Section: Related Workmentioning
confidence: 99%
“…To ensure the naturalness of a VE, the interface of a VR application should be consistent and coordinated [6]. Interactions by the traditional interactive tools like keyboard and mouse are insufficient and lag behind to completely involve the users [7][8] in interactive 3D VE. As hand gestures are adaptable and flexible, hence suitable for interactions in a VE [2,9].…”
Section: Related Workmentioning
confidence: 99%
“…This app is free and available through Google Play. Currently, more than 7,000 downloads have been exceeded in Spanish-speaking countries [55][56][57]. Alves et al (2013) presented the 'LIFEisGAME' prototype-Ipad version, a game that promotes facial emotion recognition and helps people with ASD to understand emotions so to develop empathy using real-time automatic facial expression analysis and virtual character synthesis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the current advancements in technology applications, considering non-verbal communication such as gesture recognition can produce best results for Low functioning (LF) autistic kids. There is very less work done on Applications allowing concurrent multiple users or a group of users whereas studies have shown that applications with more than one simultaneous user can have best results as it develops social interaction naturally [4]. Existing literature also shows that significant work is not done on sensory processing disorders, only one such UI is present, and it focuses on vision only [42].…”
Section: Future Workmentioning
confidence: 99%
“…Unlike the traditional interfaces, it allows the user to utilize the graphical interface in a natural way, and it also supports multi-user interaction. Therefore, making it extremely beneficial for enhancing the social skills of Autistic children [4].…”
Section: Introductionmentioning
confidence: 99%